Penerapan Augmented Reality Produk “Rangawak Atelier” sebagai Simulasi dan Promosi Produk - Rahman Syarif; Dwi Mutia Sari (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Rangawak Atelier is a furniture brand founded by Mr. Widi, combining handcrafted quality with the aesthetics and cultural identity of Minangkabau. The brand produces furniture such as chairs and tables that highlight beauty and sustainability, reflecting a spirit of adventure and social contribution. This final project aims to create promotional media in the form of Augmented Reality (AR) filters to ensure the Rangawak brand remains well-known and relevant. The 4-D Model (Define, Design, Develop, Disseminate) is employed, involving stages of definition, design, development, and dissemination. Augmented Reality allows consumers to view products in unique 3D designs through Instagram filters, thereby expanding the promotional reach without requiring additional applications. Supporting promotional media include posters, foam boards, motion graphics, postcards, Instagram reels, and catalogs, all aimed at enhancing consumer interaction with the Rangawak Atelier brand. By using these innovative AR filters, Rangawak Atelier provides a distinctive and engaging promotional tool, helping consumers visualize the products in their own spaces and thereby making informed purchasing decisions. This approach not only maintains the brand’s presence in the market but also aligns with modern marketing trends, leveraging digital technology to create a memorable and interactive consumer experience.